Training and Mentoring Strengthening Literacy and Numeracy in Recovery Learning in Musi Banyuasin Regency - Camellia; Maharani, Rizki; Kurnisar, Kurnisar; Nila Sari; Muhammad Alipraja; Nuraini, Nuraini; Alfayyad, Syahriza (Unram Journal of Community Service, 2024)
They are strengthening training and mentoring​​​ literacy and numeracy in Musi Banyuasin Regency through training and mentoring for Principals and Vice Curriculum in Junior High Schools (SMP). Based on the results of the National Assessment and the Program for International Students Assessment (PISA) 2022, post-pandemic learning recovery is essential in Indonesia, especially in improving student literacy and numeracy. This activity aims to strengthen participants' understanding and competence in designing and implementing learning that integrates literacy and numeracy by the Merdeka Curriculum. The methods used in this activity include counselling, intensive training, and assistance in designing learning tools, such as Learning Implementation Plans (RPP), learning media, and assessments. The activity also includes evaluation through pretests and posttests to measure changes in participant understanding. The results show significant improvement in literacy and numeracy understanding, with the average posttest score of participants increasing from 50 to 70. The evaluation results showed high satisfaction from participants with the material provided and its relevance to needs in the field. This activity strengthened collaboration between education managers and learning communities and positively impacted the recovery of education quality in Musi Banyuasin Regency post-pandemic. Hopefully, this activity can be sustainable in improving literacy and numeracy at the junior high school level.